A study on the effect of stroop test on the formation of students discipline by using the Heart Rate Variability (HRV) technique - Hamzah, Shahidah; Ani, Fauziah; Halim, Harliana; Saad, Shamsaadal Sholeh; Johar, Siti Sarawati; Damin, Zahrul Akmal; Jaes, Lutfan; Abdul Wahab, Muhammad Nubli (Science Publishing Corporation, 2018)
Discipline refers to self-control and individual behaviour. Other than that, discipline is an important element in the formation of integrity level. The objective of the study is to assess the effects of using the Stroop test of biofeedback protocol in order to evaluate individual level of discipline. A clinical study has been conducted on 50 participants which is the participants is a undergraduate student from Universiti Malaysia Pahang, who were divided into two groups. First group is students get high achiever and second group is students get low achierver in academic. The Heart Rate Variability (HRV) technique has been used in the assessment of this protocol. The findings show that there was a positive relationship between the Stroop test and the students discipline that those who excelled managed to get higher score of LF spectrum as compared to HF and VLF, while the students with lower achievement showed higher score of VLF and HF spectrum than LF. In conclusion, this test is one of the tests that can be used in increasing the level of individual discipline.